Multi Drug Resistant Pathogens Causing Urinary Tract Infections in Children at Kathmandu Model Hospital - Shrestha, Basudha; Gurubacharya, Rajesh Lal; Maharjan, Basanta; Shrestha, Sanjit (Journal of Nepal Paediatric Society, 2013)
Introduction: Antibiotic resistance of urinary tract pathogens has increased globally. Updated knowledge of the antibiotic resistance patterns of uropathogens in the health institutes is important for the selection of an appropriate empirical antimicrobial therapy. The aim of this study was to evaluate the multi drug resistant urinary isolates in the children from 1 to15 years and evaluate the options for empiric antibiotic therapy. Materials and Methods: The study was conducted from December 2011 to May 2012 in the Bacteriology laboratory, Kathmandu Model Hospital. Urine samples received in the laboratory were processed for routine, culture and its sensitivity. The antimicrobial susceptibility of bacterial isolates was determined following Clinical and Laboratory Standard Institute (CLSI) recommended Kirby-Bauer Disc Diffusion method. Results: Of the total 372 urine samples received in the laboratory, 60 (16.13%) showed significant growth; of which 55.0 % (33/60) were MDR isolates. Escherichia coli were the predominant isolate from urine sample. Out of 49 Escherichia coli isolates, 27 (45.0%) were Multi drug resistant. Enterococcus faecalis (N=3) was the most predominant Gram positive isolate and 66.67 % (2/3) of this organism were multi drug resistant. Among the first line drugs used against gram negative isolates, nitrofurantoin was the most effective drug followed by quinolones, while among the second line drugs; meropenem was the most effective drug followed by chloramphenicol and amikacin, whereas; nitrofurantoin (100%) was the most effective drug for Gram positive isolates followed by norfloxacin and cefotaxime. Conclusion: High percentages of multi drug resistant uropathogens were revealed in children. Nitrofurantoin was found to be the most effective drug for gram positive, gram negative and multi drug resistant isolates. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6771 J. Nepal Paediatr. SocVol.32(3) 2012 233-238